PENUMBUHAN INDUSTRI TEPUNG LOKAL MELALUI PEMBERDAYAAN KELOMPOK TANI UNTUK MENDUKUNG KETAHANAN PANGAN DI JAWA TENGAH (Studi Kasus Kabupaten Magelang Propinsi Jawa Tengah) - Lutfi Aris Sasongko; Helmy Purwanto; Renan Subantoro (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
Food security is one of strategic priorities of national development. Food is a basic need which is essential to human life. Therefore it constitutes food diversification. The research was held to study potential of local flour industry growth especially on farmer and society empowerment to strengthen Central Java food security. The research objectives are: (1) identify society perception and preference on two composition combination wheat and local flour (sweet potato) on food processed product; (2) identify potential and constraint of local flour growth development; and (3) to choose the empowerment model on technical and managerial farmer group on local flour (sweet potato) appropriate with costumer perception and preference. The research locates on Magelang Regent Province of Central Java. Collection data method was done with interview technique, Focus Group Discussion (FGD) and Rapid Rural Appraisal (RRA). While data analysis method used descriptive statistic and SWOT (Strength, Weakness, Opportunity, Threat) analyzes. From the research, could be found information about society perception and preference of two composition combination wheat flour and local flour (sweet potatoes) on food processed product was good relatively (could give score of test result which is almost same on two composition). From potential and constraint identification, the result gave that the potential of farmer group for developing local flour industry was good and strength relatively. While the model formula of farmer group empowerment which is offered to selected farmer group in Magelang Resident was empowerment with assistance, tool grant and socialization. The model was hoped could be adopted by all stakeholders. Farmer group empowerment process would be done with synergy by all stakeholders. So optimal result could be taken and the utility could be felt by farmer group on income improvement. On the turn, the effort could improve farmer wealth and strengthen the food security.